A atividade econômica e a redução das desigualdades sociais e regionais: políticas públicas e programas privados com ênfase no desporto - Masson, Aloisio (2013)
With so many economic and social changes, including the effects of the global crisis of 2008, the question arises about how to maintain economic activity and heated, while sustaining a level of social and regional development capable of reducing inequalities. The social economy and should accompany these changes in harmony, guaranteeing the right to development as an element of human dignity. All these economic and social changes, as well as its consequences, suggest the role of Economic Law in the study of state intervention in economic activity. This is how, based on doctrine and based on literature review, the scope of this study is to create a route, among many, to enable the development of regions and groups with a consequent reduction of its inequalities, once inserted into a capitalist society, but human. This is because economic activity is itself providing the increase in inequality, although the system should balance such oppression to ensure social rights to citizens. In this area of apparent collision, there is a balance of Brazilian constitutional system, between the economic and the social order, through the intervention of the state, capable of providing, on the one hand and economic development on the other, social development and regional. State intervention becomes imperative in the implementation of public policies, so it should induce the private sector to organize programs aimed at social and expansion of regional markets, which actually help to accomplish the goals Republicans and the constitutional principles of the economic order. Among these public policies and private programs that seek to reduce social and regional inequalities worth emphasizing those related to the sport, not only for social inclusion, but also for the organization of major sporting events, and attractive investment thrusters public works infrastructure which benefit whole community, promoting the regional economy still in a virtuous circle, realizing therefore social justice